Case Study : Syofia Mazalan Resources / Aida Maisarah Zakaria - Zakaria, Aida Maisarah (2021)
Regarding to fulfil Fundamental of Entrepreneurship (ENT300) course requirement, me as a student need to carry out a case study. During this case study, I need to collect all information about a company to complete this assignment, so I decided to choose Syofia Mazalan Resources. I also contact with the owner of the company to do an interview session who is Madam Nur Aliyah Syofia Binti Mohd Mazalan. From the interview I have known about their company information, which is background of the business, organizational structure, type of business model, product or services marketing and operational strategy and financial achievement.